(untitled) (Homoeopathy for All, 2025)
What’s New in Kidney Stone Research Posted on June 5, 2012 by KidneyStoners.org At the 2012 American Urological Association Annual Meeting, researchers from around the world present research on a range of urological topics, including the latest information on stone disease, prevention, and treatment. This year the meeting was in Atlanta, Georgia between May 19th and May 23rd, 2012. Drs. Jonathan Shoag and Brian Eisner presented their study, “Kidney stone prevalence is increasing in the United States over the last 2 decades: a comparison of NHANES III and NHANES 2007-2008.” The researchers used a national survey to determine the percentage of Americans reporting a history of stones.They found that compared to data from 1988- 1994, Americans in 2007 to 2008 were much more likely to report a history of stones. Overall, 8.5% of Americans report having stones in 2007-8 compared to 5.2% in 1988-1994. Among men, the current percentage is 10.6% while it is 6.4% in women. The increases in stones was seen for all racial groups.